Runoff erosion and nutrient depletion in five Mediterranean soils of NE Spain under different land use. - Pardini, Giovanni; Gispert, Maria; Dunjó, Gemma (The Science of the total environment, 2003)
We investigated the influence of agricultural management and various plant covers related to the period of abandonment on soil properties, erosion and nutrient depletion in a typical Mediterranean area with sandy loam shallow soils. Cultivated soils (CS) with insufficient management, 5 year abandoned soils covered with meadow (A5), 25 year abandoned soils covered with dense scrubs (A25), 50 year abandoned soils covered with cork trees (A50) and soils in a 50 year pine reforested area (P50) were studied over a period of 6 months (May-October 1999). The soils were classified as Lithic Xerorthents. Both the differences in soil properties and response to rainfall events were mainly attributed to the different vegetation types and stages in land management. Principal components analysis (PCA) was performed on the results, by running the overall data determined after five rainfall events. The factors extracted by PCA of the samples by variables matrix represented the response of the environments to different rainfall intensities as a function of management or natural evolution after abandonment. CS environments showed the highest runoff and sediment yield as well as the highest amount of dissolved organic carbon (DOC) and nitrogen in runoff water. The sequence of abandonment (A5, A25 and A50) showed approximately the same runoff production, whereas eroded sediments (ES) and DOC were inversely correlated. Organic carbon in the ES and DOC in runoff water always increased with the period of abandonment, which accounted for consistent nutrient depletion. Nevertheless, the A50 environment (dominated by Quercus suber) showed the best soil properties, whilst the A25 environment with dense cover of Cistus monspeliensis and Calicotome espinosa seemed to cause a worsening effect on the soil's physical and chemical properties. This is probably because these environments are more severely damaged by wild fire occurrence. In terms of sediment yield, the P50 environment followed CS environment, indicating that reforestation followed by insufficient forest management may negatively affect both soil properties and response to the erosive action of rainfall.
The following values have no corresponding Zotero field: accession-num: 12798105
Keywords: Abandonment; erosion; land management; nutrient availability; Nutrient losses; runoff; Sediment yield; soil properties; structure; Water retention

Runoff erosion and nutrient depletion in five Mediterranean soils of NE Spain under different land use. - Pardini, Giovanni; Gispert, Maria; Dunjó, Gemma (The Science of the total environment, 2003)
We investigated the influence of agricultural management and various plant covers related to the period of abandonment on soil properties, erosion and nutrient depletion in a typical Mediterranean area with sandy loam shallow soils. Cultivated soils (CS) with insufficient management, 5 year abandoned soils covered with meadow (A5), 25 year abandoned soils covered with dense scrubs (A25), 50 year abandoned soils covered with cork trees (A50) and soils in a 50 year pine reforested area (P50) were studied over a period of 6 months (May-October 1999). The soils were classified as Lithic Xerorthents. Both the differences in soil properties and response to rainfall events were mainly attributed to the different vegetation types and stages in land management. Principal components analysis (PCA) was performed on the results, by running the overall data determined after five rainfall events. The factors extracted by PCA of the samples by variables matrix represented the response of the environments to different rainfall intensities as a function of management or natural evolution after abandonment. CS environments showed the highest runoff and sediment yield as well as the highest amount of dissolved organic carbon (DOC) and nitrogen in runoff water. The sequence of abandonment (A5, A25 and A50) showed approximately the same runoff production, whereas eroded sediments (ES) and DOC were inversely correlated. Organic carbon in the ES and DOC in runoff water always increased with the period of abandonment, which accounted for consistent nutrient depletion. Nevertheless, the A50 environment (dominated by Quercus suber) showed the best soil properties, whilst the A25 environment with dense cover of Cistus monspeliensis and Calicotome espinosa seemed to cause a worsening effect on the soil's physical and chemical properties. This is probably because these environments are more severely damaged by wild fire occurrence. In terms of sediment yield, the P50 environment followed CS environment, indicating that reforestation followed by insufficient forest management may negatively affect both soil properties and response to the erosive action of rainfall.
Keywords: Abandonment; erosion; land management; nutrient availability; Nutrient losses; runoff; Sediment yield; soil properties; structure; Water retention